Multi-scale aware turbulence network for underwater object recognition - Zhou, Meng; Cai, Lei; Jia, Jishen; Gao, Yuhe (Frontiers in Marine Science, 2024)
Underwater imagery is subject to distortion, and the presence of turbulence in the fluid medium poses difficulties in accurately discerning objects. To tackle these challenges pertaining to feature extraction, this research paper presents a novel approach called the multiscale-aware turbulence network method for underwater object identification (MATNet). More specifically, the paper introduces a module known as the multi-scale feature extraction pyramid network module, which incorporates dense linking strategies and position learning strategies to preprocess object contour features and texture features. This module facilitates efficient extraction of multi-scale features, thereby enhancing the effectiveness of the identification process. Following that, the extracted features undergo refinement through comparison with positive and negative samples.Ultimately, the study introduces multi-scale object recognition techniques and establishes a multi-scale object recognition network for precise identification of underwater objects, utilizing the enhanced multi-scale features. This process entails rectifying the distorted image and subsequently recognizing the rectified object. Extensive experiments conducted on an underwater distorted image enhancement dataset demonstrate that the proposed method surpasses state-ofthe-art approaches in both qualitative and quantitative evaluations.